Diels–Alder Reactions of Masked o‐Benzoquinones with 1‐Vinylcyclohexenes: A Short and Efficient Entry to Highly Functionalized Decahydrophenanthrene Skeleton. Issue 18 (9th May 2014) - Niu, Guang‐Hao; Hou, Chieh‐Shen; Chuang, Gary Jing; Wu, Chi‐Phi; Liao, Chun‐Chen
Abstract: Masked o ‐benzoquinones (MOBs), which were generated in situ from 2‐methoxyphenols, underwent Diels–Alder reactions with 1‐vinylcyclohexenes to produce the corresponding cycloaddition products, that is, decahydrophenanthrenes along with bicyclo[2.2.2]octenones. In the former case, the MOBs serve as the dienophile, and in the later case, the 1‐vinylcyclohexenes act as the dienophile. The obtained bicyclo[2.2.2]octenones could be transformed into the corresponding decahydrophenanthrenes through a Cope rearrangement at 220 °C. Thus, these tandem reactions provide a short and efficient entry to the decahydrophenanthrene skeleton from easily available 2‐methoxyphenols. Abstract : Masked o ‐benzoquinones (MOBs), which were generated in situ from 2‐methoxyphenols, underwent Diels–Alder reactions with 1‐vinylcyclohexenes to produce the corresponding decahydrophenanthrenes and bicyclo[2.2.2]octenones. The obtained bicyclo[2.2.2]octenones could be transformed into decahydrophenanthrenes through a Cope rearrangement at 220 °C.